Prevalence of carbapenemase-encoding genes carriage in patients admitted to multidisciplinary hospital in Moscow - Ni O.G.; Shifman E.M.; Yakovlev S.V.; Bykov A.O.; Gorbacheva A.A.; Kruglov A.N.; Belotserkovskiy B.Z.; Matyushkov N.S.; Galata A.A.; Protsenko D.N. (Клиническая микробиология и антимикробная химиотерапия, 2024)
Objective.